OPTIMALISAI SUPERVISI KEPALA SEKOLAH DALAM MEREALISASIKAN PEMBELAJARAN BERKUALITAS BERBASIS KURIKULUM MERDEKA - Nida Aini; Puri Nuralyanti; Reksa Adya Pribadi; Rima Safitri (Jurnal Genta Mulia, 2024)
This research aims to find out how the school principal supervises in realizing quality learning based on the independent curriculum at SD Negri Karundang 1 Serang City. In this research, researchers used this type of research qualitative approach with descriptive methods. And in using data, researchers use observation, interview and documentation techniques. The results of research in our group show that school principals have an important role in relation to teacher competency because school principals serve as supervisors who have the obligation to supervise the work carried out by teachers, as is the case with the independent curriculum. This curriculum change must be interpreted as a beginning, not a goal. This is the beginning of the learning process to improve the quality of learning. Where to improve the quality of education in an institution, teachers are needed who truly have competence in teaching, because in essence teachers play an important role in curriculum planning and development. In this way, quality teachers will produce quality education which has implications for the birth of a quality generation so that they can compete in this era of globalization.